2004
DOI: 10.1248/bpb.27.802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Young Barley Leaf Extract and Adlay on Plasma Lipids and LDL Oxidation in Hyperlipidemic Smokers

Abstract: Atherosclerosis is the principal cause of heart attacks, strokes and gangrene of the extremities. Atherosclerotic lesions result from an excessive, inflammatory-fibroproliferative response to various forms of insults to the endothelium and smooth muscles of the artery walls.1) Previous studies have also indicated that the oxidative modification of lowdensity lipoprotein (LDL) plays a key role in the pathogenesis of atherosclerosis. 2)Cigarette smoke contains high concentrations of gaseous oxygen radicals and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…It was reported that supplementation with adlay seed and its crude extract decreased blood lipids and inhibited LDL oxidation in animals or humans 24–29. The present study demonstrated that adlay seed oil at a dose of 5 mL kg −1 could significantly reduce ( P < 0.01) the LDL‐C content in hyperlipidemic rats.…”
Section: Discussionsupporting
confidence: 63%
“…It was reported that supplementation with adlay seed and its crude extract decreased blood lipids and inhibited LDL oxidation in animals or humans 24–29. The present study demonstrated that adlay seed oil at a dose of 5 mL kg −1 could significantly reduce ( P < 0.01) the LDL‐C content in hyperlipidemic rats.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, young green barley has a broad spectrum of health-promoting properties, such as antioxidant [8,9,10,12], anti-inflammatory [10,13], anti-depressant [14], hypoglycemic [15,16] and anti-atherosclerotic [17,18,19,20]. Barley seedlings also may inhibit differentiation of osteoclasts and bone-resorbing activity in all the stages of osteoclastogenesis [21].…”
Section: Introductionmentioning
confidence: 99%
“…[23] In another study on hyperlipidaemic subjects, supplementation with 15 g of young barley leaf extract for 4 weeks substantiated the previous observations. [24] With a control group, none of the subjects being on lipid lowering medication and no significant dietary changes noted before and after supplementation, our data indicate that improvements in lipids may be due to BGP per se.…”
Section: Discussionmentioning
confidence: 61%